Pericardial Neo‐Aorta to Bridge Long Segment Defects after Infected Aortic Reconstructions123. Issue 3 (28th February 2013) - Rahman, I.A.; Angelini, G.D.; Hamilton, M.; Bryan, A.J.
ABSTRACT Aortic prosthetic graft infection is a rare, potentially fatal complication. Surgical explantation of the infected native and prosthetic material with sufficient debridement has sometimes been limited by the lack of a suitable conduit to bridge the residual long segment defect. We describe the implantation of a bovine pericardial fashioned neo‐aorta to manage this problem. doi: 10.1111/jocs.12077 (J Card Surg 2013;28:295–297)